2019
DOI: 10.5539/ibr.v13n1p268
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Organizational Performance in Nepal Airlines Corporation

Abstract: The objective of the study is to evaluate performance influencing factors in Nepal Airlines Corporation (NAC) through mixed research method, qualitative and quantitative analysis. The primary data were obtained from in-depth interview with fifteen government and NAC executives. Secondary data were collected from Nepal Government, NAC publications and International Air Transport Association (IATA).Revenue generation and passenger movement rate is found with average performance. Motivated employee, entrepreneuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Air transportation industry has been examined in previous studies from different perspectives including service quality (Chen and Liu, 2017;Perçin, 2018;Deveci et al, 2018;Farooq et al, 2018;Gayle and Yimga, 2018;Sweis et al, 2019) performance efficiency, cost and productivity (Berrittella et al, 2009;Ajayi et al, 2010;Miranda et al, 2015;Wang et al, 2017;Choi 2017Heshmati et al, 2018 social responsibility (Wang et al, 2015) operational and organizational performance (Schefczyk, 1993;Sweis et al, 2019;Kiraci and Yaşar, 2020;Gyanwali and Walsh, 2020) and financial performance (Feng and Wang, 2000;Baker et al, 2005;Teker et al, 2016;Hazarika and Boukareva, 2016;Mhlanga, 2017;Dayi and Ulusoy, 2018;Trisakti, 2018;Perçin and Aldalou, 2018;Kiracı, 2019). While, fewer studies have looked for both the financial and operational performance (Tsikriktsis, 2007;Lee, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Air transportation industry has been examined in previous studies from different perspectives including service quality (Chen and Liu, 2017;Perçin, 2018;Deveci et al, 2018;Farooq et al, 2018;Gayle and Yimga, 2018;Sweis et al, 2019) performance efficiency, cost and productivity (Berrittella et al, 2009;Ajayi et al, 2010;Miranda et al, 2015;Wang et al, 2017;Choi 2017Heshmati et al, 2018 social responsibility (Wang et al, 2015) operational and organizational performance (Schefczyk, 1993;Sweis et al, 2019;Kiraci and Yaşar, 2020;Gyanwali and Walsh, 2020) and financial performance (Feng and Wang, 2000;Baker et al, 2005;Teker et al, 2016;Hazarika and Boukareva, 2016;Mhlanga, 2017;Dayi and Ulusoy, 2018;Trisakti, 2018;Perçin and Aldalou, 2018;Kiracı, 2019). While, fewer studies have looked for both the financial and operational performance (Tsikriktsis, 2007;Lee, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Integrating the degree of assets lightness into regression analysis provides that a positive relationship excised between degree of assets lightness and dynamic efficiency. Gyanwali and Walsh (2020) considered the factors influencing performance of Nepal Airlines Corporation, and showed that the key performance factors include: motivated employee, collective leadership, entrepreneurial marketing and environmental support. They claimed thus such factors would succeed business in turbulent market.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of firm reputation in a business organization is increasing due to the public awareness about action and issues related to cooperation, higher expectation of stakeholder's, online communication, personal experience of customer on the product or services that increases the importance of managing the corporate reputation (Shamma, 2012). The organization's performance is determined by the actual output that is measured against the intended outcome of the organization (Gyanwali & Walsh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The role of business organization has been changed from profit-maximizing to the responsibility towards a society where the business is responsible to the shareholders and other stakeholders (Islam, 2012). Organizational performance indicates the success of non-economic and economic goals effectively (Gyanwali & Walsh, 2020). According to Carroll (1991), there is a hierarchy of responsibilities from economic, legal, ethical, and philanthropic.…”
Section: Introductionmentioning
confidence: 99%